Reforming China's cadre management system: two views of a civil service - Lam Tao-Chiu; Hon S. Chan (1996)
This article argues that the reform of the cadre and personnel system depends heavily on the overall political environment and, more specifically, on political structure reform in China. Although some areas of personnel management may well be technical in nature, many others are closely tied to core features of CPC powers and the established political order. The kind of civil service system proposed in the 13th Congress was possible because it was part and parcel of comprehensive reform of the political structure. With the defeat of the political structure reform, it is only natural that the civil service system has become a completely different creation from what was envisioned several years ago
Keywords: Civil service - China; Administrative reform